Sí es acoso, hazte escuchar: Campaña de difusión del protocolo contra la violencia sexual y de género de la Universidad Antonio Nariño (2023)
This project is a campaign against sexual harassment at the Universidad Antonio Nariño, aimed at disseminating the "Protocol for the prevention, detection, attention, mitigation, and follow-up of situations associated with sexual violence and gender-based violence" adopted by UAN. Since this protocol is unfamiliar to the university community, a key issue identified through Graphic Design is that the document is overly lengthy, tedious, and challenging to read. The goal is to make the information accessible and less overwhelming. The campaign took place at the Universidad Antonio Nariño during the second semester of 2023.